Debate: Making sense of the psychology of detention: A reply to Kevin Solomons: A contribution to a theory of the dynamic mechanisms of Post-traumatic Stress Disorder in South African detainees - PINS 11 - Edwards, David (PINS-Psychology in Society, 2025)
I am writing to express my disappointment at the article in Psychology in society - 11 (December 1988) entitled "A Contribution to a Theory of the Dynamic Mechanisms of Post-traumatic Stress Disorder in South African Detainees" by Kevin Solomons. At a time when the manifestations of and treatment of Post Traumatic Stress Disorder is of such serious concern, I am sure that many mental health practitioners within the country reach with interest toward any article written on the subject by people who have had practical experience. I certainly did, and therefore my disappointment on reading the article was the greater. The article contains some interesting and useful case vignettes, but it certainly does not do what it claims to do: that is make any contribution to theory. What it does is to rehash a lot of psychoanalytic concepts which are irrelevant and confusing and which make no contribution at all to our understanding of Post Traumatic Stress, let alone the particular manifestation of it found among ex-detainees.